1959
DOI: 10.1111/j.1550-7408.1959.tb04377.x
|View full text |Cite
|
Sign up to set email alerts
|

Babesia tachyglossi n. sp. from the Echidna Tachyglossus aculeatus

Abstract: SYNOPSIS. A piroplasm occurring in the erythrocytes of 38 of 42 echidnas (Tachyglossus aculeatus) has been described and named Babesia tachyglossi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1960
1960
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Babesia tachyglossi and an unspeciated Babesia sp. have also been reported in the short-beaked echidna ( Tachyglossus aculeatus ) ( Backhouse and Bolliger, 1957, 1959; Mackerras, 1959; Bolliger and Backhouse, 1960 ).…”
Section: Introductionmentioning
confidence: 81%
“…Babesia tachyglossi and an unspeciated Babesia sp. have also been reported in the short-beaked echidna ( Tachyglossus aculeatus ) ( Backhouse and Bolliger, 1957, 1959; Mackerras, 1959; Bolliger and Backhouse, 1960 ).…”
Section: Introductionmentioning
confidence: 81%
“…Plasmodium falciparum (Accession number M19172) was used as an outgroup. Maximum Likelihood (ML) analyses (1959); Priestley (1915); Seddon (1952); Seddon and Albiston (1966) Isoodon obesulus (Southern brown bandicoot) Theileria peramelis Mackerras (1959); Munday (1978Munday ( , 1988 Perameles nasuta (Long-nosed bandicoot) Theileria peramelis Mackerras (1959) Potorous tridactylus (Long-nosed potoroo) Theileria peramelis Mackerras (1959) Tachyglossus aculeatus (Short-beaked echidna) Babesia tachyglossi Backhouse and Bolliger (1959); Ristic and Lewis (1977) Isoodon obesulus (Southern brown bandicoot) Babesia thylacis Mackerras (1959) Ornithorhynchus anatinus (Platypus) Theileria sp. Mackerras (1958) Perameles nasuta (Long-nosed bandicoot) Theileria sp.…”
Section: Isolatesmentioning
confidence: 99%
“…Species of Babesia occur in a wide range of domestic and wild mammals, B.bigemina and B. bovis in cattle representing the most economically important and pathogenic species in Australia (Dawood et al 2013). Although several species of Babesia have been described or identified in dasyurid, peramelid, potoroid and macropodid marsupials as well as the echidna, reports of clinical babesiosis in wildlife have been rare (Backhouse and Bolliger 1959;Mackerras 1959;Barker et al 1978;O'Donoghue and Adlard 2000;Paparini et al 2012;Dawood et al 2013;Donahoe et al 2015b). Disease is associated with infections in male antechinus with physiological stress in the postmating period (Cheal et al 1976;Barker et al 1978) and has been reported in eastern grey kangaroos with neurological signs, depression and anaemia attributed to stress due to handling, transportation and captivity (Dawood et al 2013).…”
Section: Piroplasmida Babesiamentioning
confidence: 99%